2016
DOI: 10.1098/rspb.2015.2911
|View full text |Cite
|
Sign up to set email alerts
|

Multigenerational exposure to silver ions and silver nanoparticles reveals heightened sensitivity and epigenetic memory inCaenorhabditis elegans

Abstract: The effects from multigenerational exposures to engineered nanoparticles (ENPs) in their pristine and transformed states are currently unknown despite such exposures being an increasingly common scenario in natural environments. Here, we examine how exposure over 10 generations affects the sensitivity of the nematode Caenorhabditis elegans to pristine and sulfidized Ag ENPs and AgNO 3 . We also include populations that were initially exposed over six generations but kept unexposed for subsequent four generatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
55
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 41 publications
3
55
0
Order By: Relevance
“…Together, our results underscore the importance of considering transgenerational plasticity not only when assessing the impact of warming (e.g., Donelson et al., ; Shama et al., ; Veilleux et al., ) and of pollutants (e.g., Costa et al., ; Pölkki et al., ; Schultz et al., ), but also when considering the impact of pollutants in a warming world. Our results thereby highlight the importance of integrating the emerging views of multistressor studies (Liess et al., ; Stoks, Geerts, & De Meester, ) and studies on transgenerational plasticity (Donelson et al., ; Guillaume et al., ) to understand the fate of species under global change.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Together, our results underscore the importance of considering transgenerational plasticity not only when assessing the impact of warming (e.g., Donelson et al., ; Shama et al., ; Veilleux et al., ) and of pollutants (e.g., Costa et al., ; Pölkki et al., ; Schultz et al., ), but also when considering the impact of pollutants in a warming world. Our results thereby highlight the importance of integrating the emerging views of multistressor studies (Liess et al., ; Stoks, Geerts, & De Meester, ) and studies on transgenerational plasticity (Donelson et al., ; Guillaume et al., ) to understand the fate of species under global change.…”
Section: Discussionsupporting
confidence: 57%
“…Again, these differences may be due to the magnitude of the warming imposed (Donelson et al., ). Also for contaminants, there is mixed evidence in invertebrates: some studies showed parental exposure increasing the tolerance of the offspring (e.g., Brausch & Salice, ; Kim et al., ; Reátegui‐Zirena et al., ), while other studies showed the opposite (Pölkki et al., ; Schultz et al., ; Yu et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of such mechanism is epigenesis. Histome modification, another epigenetic mechanism, caused inhibition of vulval development in C. elegans (Andersen and Horvitz 2007;Schultz et al 2016). For example, the earthworm Lumbricus rubellus from an arseniccontaminated field soil tolerated arsenic exposure because its altered DNA methylation was transferred from the parents (Kille et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to epigenesis, multigenerational exposure can cause teratogenesis, in which the embryo or fetus is malformed due to embryo exposure to chemicals (Vargesson and Fraga 2017). There can also be a direct maternal transfer of metals to other generations (Kim et al 2013;Schultz et al 2016). For example, exposure to lead caused leg malformation in the larval and nymphal stage of the mite A. longisetosus (Kohler et al 2005).…”
Section: Introductionmentioning
confidence: 99%